A utilização de ERP em contexto de Ensino Superior - Aparicio, M. (2018)
Enterprise Resource Planning (ERP) systems are the corner stone of organizational information systems. ERP usage in higher education is an opportunity that universities have undertaken to achieve students' performance, employment, satisfaction, and align with the labor market. This paper evaluates if the usage of an ERP in higher education context improves the management learning nearer to the market requisites. To perform this evaluation, it was developed a syllabus plan aiming to provide a solid theoretical background on organizational information systems and also providing interaction with a real ERP in classes. Followed by a qualitative study method to infer the students' knowledge on management key concepts and ERP usage in general.